Improving the N-glycosylation occupancy of plant-produced IgG1 by engineering the amino acid environment at Asn297 - Göritzer, Kathrin; Ruocco, Valentina; Vavra, Ulrike; Izadi, Shiva; Bolaños-Martínez, Omayra C.; Phetphoung, Thareeya; Pisuttinusart, Nuttapat; Phoolcharoen, Waranyoo; Strasser, Richard (Frontiers in Plant Science, 2025)
Monoclonal antibodies are crucial recombinant biopharmaceuticals, with N-glycosylation at Asn297 essential for their functionality. Plants are increasingly used for antibody production, achieving high expression levels and enabling glycoengineering to produce homogenous human-like N-glycan structures. However, plant-produced human IgG1 often shows significant underglycosylation with potential adverse effects for immune functions and stability. This study addressed this limitation of the widely used plant-based expression platform Nicotiana benthamiana by employing protein engineering to enhance N-glycosylation occupancy in plant-produced IgG1. This was achieved through an amino acid mutation near the conserved glycosylation site in the CH2 domain of the heavy chain. The transient expression of trastuzumab and SARS-CoV-2 neutralizing IgG1 antibody COVA2-15 in N. benthamiana, with mutations such as Y300L, resulted in a notable improvement in glycosylation occupancy. While the structural integrity and monodispersity of the IgG1 variant remained unaltered, an improvement in thermal stability was observed. Furthermore, functional assays showed that antigen binding and human hFcRn interaction were unaffected, while FcγRIIIa binding affinity increased. These findings demonstrate the potential of protein-engineering to enhance the quality and functionality of plant-produced IgG1 antibodies, making them comparable to mammalian-produced counterparts.